APPROXIMATION OF AN ELECTRIC SHOCK ABSORBER MATHEMATICAL MODEL PARAMETERS - Sergienko, A. N.; Liubarskiy, B. G.; Sergienko, N. E. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2013)
The paper introduces a procedure of approximating polynomial calculation to allow identifying magnetic linkage and electromagnetic force of an electric shock absorber mathematical model.